Factors Related to Elderly Anxiety in Health Problems in the Working Area of the Antara District Health Center - Syahrir; Fatmawati (Jurnal Penelitian Pendidikan IPA, 2023)
Elderly (elderly) is not a disease but an advanced stage of the process of human life, even though it is not a disease, this condition can cause physical, social and mental problems. This type of research is an analytic survey, with a cross-sectional research design. The population in this study were all elderly people living in the Work Area of the Antara Health Center. The samples taken were 34 people, which were obtained using the Accidental Sampling technique. The data obtained in this study were processed using the Chi-Square statistical test with a fisher's exact test correction. The results showed knowledge (p=0.002), and education (p=0.008), and family support (p=0.002).Â  In this study it can be concluded that there is a relationship between knowledge and prevention of anxiety in the elderly in health problems, there is a relationship between education and prevention of anxiety in the elderly in health problems and there is a relationship between family support and prevention of anxiety in the elderly in health problems. Suggestions in this study are that it is hoped that health workers can provide counseling about elderly health as an effort to increase knowledge in the elderly about preventing elderly anxiety in the health problems they face and families can always provide support for the elderly.